The religious influence on the evangelical vote: a quantitative and sociological analysis based on field research - Gomes, Maria Laura Rodrigues; Rosa, André Felipe (Revista Coleta Científica, 2024)
The political decision-making process is marked by a complex network of social interactions, community influences and opinion leaders. This article investigates the phenomenon of evangelical voting in Brazil, analyzing the influence of religious leaders on the voting behavior of their faithful. Based on the theories of Paul Lazarsfeld and collaborators, such as The People’s Choice (1944), Personal Influence (1955) and Voting: A Study of Opinion Formation in a Presidential Campaign (1957), this study employs a quantitative approach to understand the impact of religious leaders and the role of two-level communication in shaping electoral choices. The data reveals that the greater the participation of believers in religious activities, the greater the likelihood that their political decisions will be shaped by religious leaders. It is concluded that the evangelical vote reflects not only an individual choice, but a deeply social and community phenomenon, mediated by religious interactions that reinforce moral and political values.